The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11104-008-9628-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant symbiotic microorganisms in acid sulfate soil: significance in the growth of pioneer plants

Abstract: Acid sulfate soil is generated by chemical and microbial oxidization of sulfide-rich minerals/sediments. Although revegetation of the soil is difficult due to low-pH and poor nutrient availability, pioneer plants may adapt to such an extreme environment via associating with mycorrhizal fungi and/or N-fixing bacteria for acquisition of mineral nutrients. In this study, an abandoned quarry in which acid sulfate soil was found was chosen to investigate the influence of soil acidity on the levels of colonization b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…For the marsh plant Spartina spp., it has been shown that the combination of proton toxicity and concomitant mobilization of Al may have contributed to die-off events during droughts (McKee et al, 2004). It has been suggested that acid-tolerant arbuscular mycorrhizal fungi may play an important role in the establishment of pioneer species (grasses, forbs and shrubs) on dry acid sulfate soils (Maki et al, 2008). …”
Section: Indirect Toxicity During Drought Of Sulfidic Wetlandsmentioning
confidence: 99%
“…For the marsh plant Spartina spp., it has been shown that the combination of proton toxicity and concomitant mobilization of Al may have contributed to die-off events during droughts (McKee et al, 2004). It has been suggested that acid-tolerant arbuscular mycorrhizal fungi may play an important role in the establishment of pioneer species (grasses, forbs and shrubs) on dry acid sulfate soils (Maki et al, 2008). …”
Section: Indirect Toxicity During Drought Of Sulfidic Wetlandsmentioning
confidence: 99%
“…AMF occur in acid soils, even with such low pH-values of 2.7 (Cumming and Ning, 2003;Maki et al, 2008;Taheri and Bever, 2010;Seguel et al, 2013) and can be symbiotically cultivated under such conditions (Cavallazzi et al, 2007;Hu et al, 2013). Spores of Acaulospora laevis occur in soil of very low pH, whereas Glomus sp.…”
Section: The Role Of Symbiotic Fungi In Determining the Plant Communimentioning
confidence: 99%
“…Soil acidity also constrains plant productivity; inhibition of root elongation and reduction of phosphorus (P) solubility in the soil solution lead to serious P deficiency in plants [ 6 , 7 , 8 ]. Arbuscular mycorrhizal (AM) fungi are the obligate biotrophs that associate with most land plants, deliver phosphorus (P) to the host plant [ 9 ], and thus play a significant role in the establishment of early-successional species in acidic soil [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%